2018
DOI: 10.11604/pamj.2018.31.82.14725
|View full text |Cite
|
Sign up to set email alerts
|

Hépatite virale B: aspects cliniques, paracliniques et évolutifs dans le service d’Hépato Gastroentérologie de l’Hôpital Aristide Le Dantec: à propos de 728 cas

Abstract: L’hépatite virale B constitue un problème majeur de santé publique en Afrique subsaharienne avec environ 65 millions de porteurs chroniques et 56.000 décès par an. Notre étude avait pour but d’étudier les aspects épidémiologiques, paracliniques, thérapeutiques, évolutifs des patients atteints d’hépatite virale B suivis dans notre service et de décrire leurs profils sérologiques. Nous avons réalisé une étude rétrospective, longitudinale de 2010 à 2014 dans le service d’hépato gastroentérologie de l’hôpital Aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…According to the clinical signs, liver ultrasound and Fibrotest* we found 19.4% cirrhosis at diagnosis. This result is similar to the one reported by Diallo S. et al in Senegal (22.11%) [16] but lower than the one found by Lawson et al…”
Section: Discussionsupporting
confidence: 90%
“…According to the clinical signs, liver ultrasound and Fibrotest* we found 19.4% cirrhosis at diagnosis. This result is similar to the one reported by Diallo S. et al in Senegal (22.11%) [16] but lower than the one found by Lawson et al…”
Section: Discussionsupporting
confidence: 90%
“…This same observation was made by Agbenu et al Open Journal of Gastroenterology in Togo [11]. Diallo et al in Senegal found a sex ratio of 2.2 [9].…”
Section: Discussionsupporting
confidence: 82%
“…Amidu et al in Ghana found an age of 37.93 ± 0.93 years [8]. On the other hand Diallo et al in Senegal found a mean age of 33 years [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the one hand, the unfavorable socioeconomic level is more impacted by CHB [ 85 ]. On the other hand, the socioeconomic profile of our NC-CHB patients is representative of African patients with CHB [ 86 ]. According to a Senegalese study [ 86 ], due to socio-economic difficulties, the serological status was undetermined in 34.6% of patients.…”
Section: Methodology Discussion and Study Limitationsmentioning
confidence: 99%
“…On the other hand, the socioeconomic profile of our NC-CHB patients is representative of African patients with CHB [ 86 ]. According to a Senegalese study [ 86 ], due to socio-economic difficulties, the serological status was undetermined in 34.6% of patients. The third limitation is related to the non-practice of the HBV-DNA test and a fibroscan in the control group to confirm the absence of HBV and hepatic fibrosis, respectively.…”
Section: Methodology Discussion and Study Limitationsmentioning
confidence: 99%